Does funding huge capital outlay projects through project finance enhance shareholders' value? - Mheyamwa, John (Research of GSB, 2018)
Despite project finance advancing as a crucial tool in funding huge capital outlay projects that facilitate development little research has been conducted in assessing whether it is the most optimum way of funding big project especially when one looks at the value addition in respect of the shareholders. Consequently, this research attempts to examine whether Project Finance when compared to conventional funding done under Corporate Finance does contribute to shareholders value in funding huge capital outlay projects. The research was conducted in two phases. The first phase analysed the Mozal Project which was jointly funded by the IDC and other parties under project finance. In this phase the research assess how the IDC as a funder established measures to protect and enhance value for its shareholders in funding the project. The phase goes further by assessing the value created by the investment from an IDC shareholder point of view. The results are then compared to that of other high capital magnitude projects funded under on balance sheet finance. The second phase comprised of 5 interviews and 25 questionnaires with local Project Finance industry professionals with the aim of establishing the common view on which between on balance sheet and off balance sheet finance has a positive impact on shareholders' value. The first phase led to a general guide on funding projects via project finance does add to shareholder value or not whilst the second phase gave a factual conclusion on whether funding shareholder value through project finance creates value. Specific recommendations for further research work was also indicated where it was felt that there are certain areas that can help in advancing the research subject.